Left Atrial Drainage of the Right Superior Vena Cava: A Case Report - Maryam Moradian; Hojjat Mortezaeian; Ramin Baghaei; Behshid Ghadrdoost (Journal of Tehran University Heart Center, 2018)
An isolated right superior vena cava (RSVC) draining into the left atrium represents a very rare congenital malformation, especially in the absence of a partial anomalous pulmonary venous return. This condition leads to hypoxemia, cyanosis, and clubbing without any other signs of heart defects. We describe an 8-year-old girl, who was referred to our hospital due to unexplained cyanosis. Segmental approach in transthoracic echocardiography showed left atrial drainage of the RSVC, which was subsequently confirmed by contrast echocardiography and angiography. Surgical repair via trans-section and anastomosis of the superior vena cava to the right atrium was performed to prevent the complications of right-to-left shunting and cyanosis. During a 4-year follow-up, the patient remained in very good clinical status and her serial echocardiography was normal except for very mild left atrial and left ventricular enlargement.